Effects of ultrasonic vibration on sapphire polishing investigated by molecular dynamics. (December 2022) - Xu, Wenhu; Sheng, Chong; Zhong, Min
Abstract: Molecular dynamics (MD) was used to explore the influences of ultrasonic vibration on sapphire polishing, including scratching force, average friction coefficient, surface topography, number of removed atoms, temperature and subsurface damage, and reveal its micro-mechanism in this paper. The results show that the tangential and normal forces decrease gradually and the temperature increases with the rising vibration frequency. At a larger amplitude, removed atoms increase significantly but the subsurface damage is more severe. Under 25 GHz frequency and 5 Å amplitude, the subsurface damage layer is the thinnest and removed atoms are high. Moreover, the effects of velocities on sapphire ultrasonic scratching were also discussed. The sapphire removal and the surface and subsurface quality are all good at 100 m/s.